Research Probe “My Home”, Artist-based Research / in Search of Language to Interpret Perceived and Experienced Space - Gajdošíková, Pavla (Revija za elementarno izobraževanje, 2018)
In the research probe “My Home,” we investigated students’ statements about and how they experience their relationship to a particular place: home. The subject of this exploration is the mutual overlap among architecture, works of art and art education, and their common language across these fields. The character of our research was inspired by phenomenological approaches. We chose methodologies related to art and design creation. We arrived at the conclusion that the phenomenology of architecture investigated in connection with the semiotic concept of art education can yield much inspiration and is a topic relevant to both the teaching artist and students.DOI: 10.18690/rei.11.2.159-173.2018COBISS-ID:
Keywords: architecture; creative reflection; experience interpretation; methods in pedagogy; spatial forms